Mutational engineering, growth selection, expression, purification and crystallization of ligand bound endo-beta-N-acetylglucosaminidase T (Endo-T) from Hypocrea jecorina - Digre, Andreas (SLU/Dept. of Molecular Biology (until 131231), 2010)
Recently, one of the first fungal-expressed, deglycosylating, Endo-beta-N-acetylglucosaminidases was found in the extracellular medium of soft-rot ascomycete Hypocrea jecorina (a.k.a. Trichoderma reesei) belonging to glycoside hydrolase family 18 (GH18). It was named Endo-T and has been shown to possess similar substrate specificities as Endo-H from Streptomyces plicatus, a deglycosylating enzyme, frequently used in the field of glycoproteomics. In this study an oligomannosidic N-glycan was introduced in the active site of crystallized Endo-T under acidic pH conditions below pH 3. The ligand-containing crystal diffracted on a synchrotron x-ray source to a resolution of 1.65Å. The resulting Endo-T structure was found to contain a bound ligand consisting of a hydrolyzed Manα1-6(Manα1-3)Manα1-6Manβ1-4GlcNAc N-glycan, lacking the aspargine linked N-acetylglucosamine residue of N-glycans. Furthermore, electron density was missing for several of the distal glycone mannose residues. The anomeric carbon of the distal N-acetylglucosamine residue was found to be positioned 6.88Å from the proposed catalytic amino acid residue, Glu131, indicating a descending motion during hydrolysis. An unidentified electron density was found after the last structure refinement, apparently shaped as a furanose ring, next to the N-glycan ligand in the active site around unit 8 of the (β/α)8-barrel. Proximal substrate positioning and the loop-structure of Endo-T suggests aglycone docking centered over (β/α)8-barrel unit 5.